Shooting Control Application from a Quadruped Robot with a Weapon System via Sliding-mode Control Method - Tatar, Ahmet Burak; Tanyildizi, Alper Kadir; Yakut, Oguz (Defence Scientific Information Documentation Centre, 2020)
With the developing technological process, it is expected that the usage of robots will increase in defense systems as in every field. One of the main objectives of the robotic studies for the defense industry is to capture the targeted success under all kinds of disruptive effects with robotic systems and to present this technology to the service of the army. A weapon system with a single degree of freedom was placed on a quadruped robot. System's dynamic behavior, which has 12 degrees of freedom and planar movements, is modeled mathematically. Simulations of the shots made to the fixed targets were carried out during the walking of the quadruped robot. The gun barrel stabilization was realized to achieve accurate shots under disruptive effects. The sliding-mode control method was used to perform the barrel stabilisation. In this study, it is shown that a quadruped robot with a weapon system can perform successful shots against fixed targets. MATLAB is used for simulations and the results are shown with figures, graphics, and tables.
Keywords: Sliding-mode control; Target shooting; Barrel stabilisation; Quadruped robot